The Effect of Bending Deformation on Charge Transport and Electron Effective Mass of p‐doped GaAs Nanowires. Issue 8 (7th May 2019) - Zeng, Lunjie; Kanne, Thomas; Nygård, Jesper; Krogstrup, Peter; Jäger, Wolfgang; Olsson, Eva
Abstract : The crystal and electronic structure of semiconductor nanowire systems have shown sensitive response to mechanical strain, enabling novel and improved electrical, and optoelectrical properties in nanowires by strain engineering. Here, the response of current–voltage ( I – V ) characteristics and band structure of individual p‐doped GaAs nanowires to bending deformation is studied by in situ electron microscopy combined with theoretical simulations. The I – V characteristics of the nanowire change from linear to nonlinear as bending deformation is applied. The nonlinearity increases with strain. As opposed to the case of uniaxial strain in GaAs, the bending deformation does not give rise to a change in the band gap of GaAs nanowire according to in situ electron energy loss spectroscopy (EELS) measurements. Instead, the response to bending deformation can be explained by strain induced valence band shift, which results in an energy barrier for charge carrier transport along the nanowire. Moreover, the electron effective mass decreases as the strain changes from compressive to tensile across the GaAs nanowire in the bent region. Results from this study shed light on the complex interplay between lattice strain, band structure, and charge transport in semiconductor nanomaterials. Abstract : Bending strain is used to modify the charge transport in p‐doped GaAs nanowires through the development of an energy barrier for charge carriers. The sensitive response of the band structure and electrical transport property of GaAs nanowires to bending deformation shows the potential for their use in flexible electronics and sensors.